Pemikiran dan Gerakan Amr Maâ€˜rÃ»f Nahy Munkar Front Pembela Islam (FPI) di Indonesia 1989-2012 - Anwar, Saeful (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article explores the history of thoughts and movements of the Front Pembela Islam (FPI) in Indonesia between 1998 and 2012. The study concludes that since many government regulations are violated by the public, including the prohibition of gambling, prostitution and other forms of disobedience and lack of firmness of the government, FPI feels the need to take the initiative to help the government fight against immorality in order to enforce amr ma?rûf nahy munkar. This is done through the movement run by the military force of the FPI who often uses means of violence. In line with this study, FPI should not perform nahy munkar movement using any violent means, such as damaging public facilities, hurting people, and other destructive deeds. The reason is that by doing such violent actions, FPI will not even help resolving the moral problems that occur in Indonesia. In addition, the violent movement does not reflect the image of Islam as a religion of peace.